The New England image - Chamberlain, Samuel (Hastings, 1962)
Photographs of New England - the countryside, famous houses, covered bridges, water mills, historic landmarks, etc.
Keywords: Historic buildings -- New England -- Pictorial works; New England -- Pictorial works